1995
DOI: 10.1007/bf00270584
|View full text |Cite
|
Sign up to set email alerts
|

Macroamylasemia associated with ulcerative colitis

Abstract: We describe a very rare case in which macroamylasemia was associated with ulcerative colitis of total colitis type. The patient's serum amylase isozyme pattern by electrophoresis showed a broad abnormal peak toward the side of the positive pole compared with regular salivary and pancreatic fractions. Sephadex G-200 column chromatography showed a sedimentation coefficient of 6.6 S. Amylase activity was bound to IgG. Double diffusion experiments demonstrated that amylase activity could be precipitated in gel by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…8) The coexistence of macroamylasemia with multiple diseases such as ulcerative colitis, Crohn's disease, hematologic malignancies, systemic lupus erythematosus, and rheumatoid arthritis has been reported. 9) Several studies have observed the association between macroamylasemia and celiac disease as well as the disappearance of macroamylasemia with a gluten-free diet. 10) In this case, macroamylasemia was not considered in the initial differential diagnosis due to its rarity, which led to an extensive investigation.…”
Section: Discussionmentioning
confidence: 99%
“…8) The coexistence of macroamylasemia with multiple diseases such as ulcerative colitis, Crohn's disease, hematologic malignancies, systemic lupus erythematosus, and rheumatoid arthritis has been reported. 9) Several studies have observed the association between macroamylasemia and celiac disease as well as the disappearance of macroamylasemia with a gluten-free diet. 10) In this case, macroamylasemia was not considered in the initial differential diagnosis due to its rarity, which led to an extensive investigation.…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro caso, se realizó endoscopia con toma de biopsia con 6 muestras y se encontró un MARSH 0, sin criterio para ampliar el estudio de enfermedad celíaca. En cuanto a las otras patologías asociadas están las enfermedades hepáticas crónicas (17), la diabetes mellitus (18), la artritis reumatoide (19), el lupus eritematoso sistémico (20), el linfoma de células T (21), la enfermedad inflamatoria intestinal (22), el VIH asintomático (23) y el carcinoma de células renales y tiroides (16). Todas estas patologías fueron descartadas en nuestra paciente.…”
Section: Discussionunclassified
“…Prema jednoj hipotezi, koja nema potvrdu, bolovi u trbuhu i makroamilazemija otkrivaju se zajedno zbog taloženja molekula makroamilaze u pankreasu [13]. Problem u dijagnostici predstavlja moguća istovremena pojava makroamilazemije i drugih patoloških stanja poput ulceroznog kolitisa [17], Crohnove bolesti [18], hematoloških maligniteta [19,20], sistemskog lupus eritematozusa [21], reumatoidnog artritisa [22] ili celijakije [23,24,25]. Objavljeno je nekoliko slučajeva obolelih od celijakije sa makroamilazemijom kod kojih je došlo do normalizovanja amilazemije nakon lečenja dijetom bez glutena [26] [27] Teorija nastanka makro molekula amilaze se zasniva »disregulaciji« imunske tolerancijee, koja se može pojaviti kod imunskih poremećaja [28].…”
Section: Iakounclassified